2005
DOI: 10.1200/jco.2005.06.944
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Subunit of Human Telomerase Reverse Transcriptase Is an Independent Predictor of Survival in Patients Undergoing Curative Resection of Hepatic Colorectal Metastases: A Multicenter Analysis

Abstract: hTERT nucleolar expression is associated with worse survival after resection of hepatic CRM. hTERT expression in conjunction with number of hepatic metastases and disease-free interval may permit more accurate prediction of survival after resection of hepatic CRM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 45 publications
2
29
0
1
Order By: Relevance
“…However, we were not able to identify any amino-acid sequence similarity between the two proteins that could have the immunological properties of NCL-hTERT, and the question of this misrecognition remains non-elucidated. Nevertheless, the identification of nucleolin as the protein recognized by NCL-hTERT antibody should lead to an urgent re-evaluation of the results obtained with this antibody and that are already published (Brustmann, 2005;Dalerba et al, 2005;Domont et al, 2005;Dutu et al, 2005;Elkak et al, 2005;Falchetti et al, 2003;Fullen et al, 2005;Gulmann et al, 2005;Kraemer et al, 2003;Lantuejoul et al, 2005;Lantuejoul et al, 2004;Luzar et al, 2005a;Luzar et al, 2005b;Maes et al, 2005;Sabah et al, 2004;Sato et al, 2004;Smith et al, 2004;Uziel et al, 2005;Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were not able to identify any amino-acid sequence similarity between the two proteins that could have the immunological properties of NCL-hTERT, and the question of this misrecognition remains non-elucidated. Nevertheless, the identification of nucleolin as the protein recognized by NCL-hTERT antibody should lead to an urgent re-evaluation of the results obtained with this antibody and that are already published (Brustmann, 2005;Dalerba et al, 2005;Domont et al, 2005;Dutu et al, 2005;Elkak et al, 2005;Falchetti et al, 2003;Fullen et al, 2005;Gulmann et al, 2005;Kraemer et al, 2003;Lantuejoul et al, 2005;Lantuejoul et al, 2004;Luzar et al, 2005a;Luzar et al, 2005b;Maes et al, 2005;Sabah et al, 2004;Sato et al, 2004;Smith et al, 2004;Uziel et al, 2005;Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The most salient points are herein reported. A new mouse monoclonal antibody (Novocastra, NCL-hTERT, clone 44F12) has been widely used, based on the assumption that this antibody correctly recognizes the protein peptide against which it has been claimed to be developed (Brustmann, 2005;Dalerba et al, 2005;Domont et al, 2005;Dutu et al, 2005;Elkak et al, 2005;Falchetti et al, 2003;Fullen et al, 2005;Gulmann et al, 2005a;Kraemer et al, 2003;Lantuejoul et al, 2005;Lantuejoul et al, 2004;Luzar et al, 2005a;Luzar et al, 2005b;Maes et al, 2005;Sabah et al, 2004;Sato et al, 2004;Smith et al, 2004;Uziel et al, 2005;Yan et al, 2004). Using this antibody, we confirmed on western blots, as previously shown, the labelling of a unique protein band in the 100 kDa area, which is generally thought consistent with the estimated molecular weight of telomerase of 127 kDa (Wick et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Using a mouse monoclonal anti-hTERT antibody (clone 44F12, Novocastra), recent studies indicated that nucleolar expression of hTERT is associated with worse survival and is a better predictor than established clinical indicators in patients undergoing curative hepatic resection for colorectal metastases (31,32), whereas others showed that nucleolar hTERT expression is associated with better survival of patients with urothelial bladder cancer (33). However, this antibody (clone 44F12) has been shown to recognize nucleolin, but not hTERT (25).…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase activity has been reported as an independent predictor of survival of patients with varying malignancies, such as neuroblastoma (36,37), meningioma (38), breast cancer (39) and hepatic metastases of colon carcinoma (40). Studies on the potentially prognostic value of telomerase activity or hTERT expression in tumours of surgically treated lung cancer patients have, however, yielded conflicting results (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%